2013
DOI: 10.1093/rof/rfs050
|View full text |Cite
|
Sign up to set email alerts
|

Another Look at the Stock Return Response to Monetary Policy Actions*

Abstract: I analyze the effect of monetary policy actions on the cross-section of equity returns. Based on earlier theoretical work for the monetary transmission mechanism one can argue that changes in monetary policy should produce differentiated effects on firms and stocks with different characteristics. By using different portfolio sorts the results show that the impact of monthly changes in the Federal funds rate is greater for the returns of more financially constrained stocks (e.g., small and value stocks) than on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
42
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 112 publications
10
42
0
2
Order By: Relevance
“…Our results are similar to Kontonikas (2006), Taboga (2009), Mustafa, et al (2013), Maio (2014) and. The results of VAR also suggest this impact to be true among stock market and bond market with monetary policy components.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are similar to Kontonikas (2006), Taboga (2009), Mustafa, et al (2013), Maio (2014) and. The results of VAR also suggest this impact to be true among stock market and bond market with monetary policy components.…”
Section: Resultssupporting
confidence: 93%
“…It can be concluded that many studies have found that the monetary transmission mechanism is rapid and effective (Taboga, 2009). However, many other studies (Edelberg, and Marshall, 1996;Gourio, 2013;and Maio, 2014) have observed that the impact of monetary policy interest rates on market interest rates is uncertain both in developed and developing economies. Therefore, it generates the need to examine the impact monetary policy on asset prices in the context of developed and developing economies.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned system of equations is estimated at an equationby-equation basis using Ordinary Least Squares (OLS) as in Maio (2014). 11 See Table C2 in the Supporting Information for a list of the relevant announcements by the Fed.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we consider two interest rates series (the change in the Federal Funds rate and the 10-year to 3-month government bond term structure), a measure of output, inflation and the money supply. Following, for example, Thorbecke (1997), Rigobon and Sack (2004), Bernanke and Kuttner (2005) and Maio (2014) there is believed to be a negative relation between changes in the Federal funds rate and stock returns. Regarding the term structure, an increase in its value is consistent with higher expected future inflation and a monetary tightening.…”
Section: Data Choice and Motivationmentioning
confidence: 99%